Employing dialogue aesthetically in Iraqi drama (Al-Academy, 2024)
Dialogue is considered one of the basic pillars of dramatic construction. Through it، we can learn about the main idea of the dramatic work. It also reveals the dimensions of the characters and the nature of the conflict they are engaged in. A good dramatist is the one who can write beautiful، eloquent dialogue that includes intellectual، aesthetic، and dramatic values. Therefore، the goal of the current research is to identify how to (employ dialogue aesthetically in Iraqi drama). To achieve this goal، the researcher used the descriptive research approach and chose a purposive sample، which is an Iraqi series (Khan Al-Dhahab). The researcher prepared an analysis tool that was approved by a group of experts in the field of cinematic arts and television، and after the analysis The researcher reached a number of results، the most important of which are:Dramatic dialogue contributes to revealing the values and ideas held by the character.The dialogue sentences in the series (Khan Al-Dhahab) were short، eloquent، and focused on action and idea.Dialogue contributed to pushing the conflict towards a climax and then a solution.The author of (Khan Al-Dhahab) adopted the realistic style in writing dialogue، especially poetic realism and poetry.The dialogue in the series (Khan Al-Dhahab) contributed to revealing the dimensions of the characters and their goals and advancing them